“Plan de marketing para la Empresa Colrest S.A. (Restaurante Columbia) en la ciudad de Quito”. - Navarrete Arroyo, Gabriela Monserrat (2014)
In Ecuador the consumption of meat, chicken and sausage is high because of its large number of proteins and nutrients makes it necessary for adequate food and are within the foods onforman the basket. For this reason is that food restaurants have increased.